Regulation of Short-Term Rentals: Addressing Cape Cod's Housing Crisis - Kelly, Brianna. (Tufts University. Tisch Library., 2024)
Thesis (M.A.)--Tufts University, 2024.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Christine Cousineau.; Committee: Shomon Samsuddin.; Keyword: Urban planning.